Pitch perfect : a study on the influence of musician type on linguistic pitch processing - Bong, Jacqueline Michelle Mei-En (2016)
The current study explores the effects of wind musicians vs. percussionists on linguistic tone processing. English-Chinese Singaporean bilingual undergraduates aged between 22 and 25 who are all musicians playing either a wind musician or a percussive instrument completed a series of Cantonese tone perception and production tasks. Besson et al. (2007) found that musically trained individuals were better at pitch discrimination tasks in both music and speech tasks, especially in conditions where the two contrasting pitches being tested showed only slight acoustic dissimilarity rather than very overt differences. Other studies are mainly focused on comparing differences between musicians and non-musicians. This study investigates the within-musician effects on linguistic pitch processing because learning different types of instruments requires varying types of cognitive and motor development. However, no significant differences were found between the two musician groups in the Cantonese perception task. Furthermore, percussionists outperformed wind musicians despite the prediction that wind musicians were more likely to be more sensitive towards pitch owing to the differing nature of their instruments. This suggests musician type may not be a robust factor in predicting performance on linguistic pitch discrimination. This study points out improvements that can be made to further test this finding on a wider scale.